A review on the rheological behavior and formulations of ceramic suspensions for vat photopolymerization - Camargo, Italo Leite de; Morais, Mateus Mota; Fortulan, Carlos Alberto; Branciforti, Marcia Cristina (Ceramics international, 2021)
Vat photopolymerization is an additive manufacturing process that produces high-performance ceramic parts. A critical step in the process is the preparation of a suspension that meets the requirements of high ceramic loading and proper rheological behavior, since an increase in solid loading might compromise the suspension rheology, resulting in non-uniform layer recoating. This review examines the rheological behavior of ceramic suspensions for vat photopolymerization, discussing the influence of the suspension formulation (solid loading, ceramic particle size and size distribution, monomers, diluents, and dispersants) on rheological aspects such as viscosity, shear-thinning/thickening behavior, critical shear rate, yield stress, and thixotropy. It provides a summary of the best formulations, which achieved low viscosity (<3 Pa.s) and high solid loading (>40 vol%), and reports the main trends and challenges of ceramic vat photopolymerization, suggesting general guidelines for the preparation of highly loaded photocurable ceramic suspensions with low viscosity.